The Model of Formation of Patriotism at Schoolchildren by Means of Folk Pedagogics - Diana N. Davletbaeva; Elena L. Iakovleva; Diana F. Kajumova; Anna A. Karimova; Aida G. Sadykova; Elena V. Shvetsova; Elmira M. Vildanova; Dariya Z. Yarhamova (International Review of Management and Marketing, 2016)
The topicality of the study of the problem is due to the fact that the sharp change in the hierarchy of values, priorities, ideals, lack of spirituality, lack of morality, the unleashing of military conflicts, extremism and clash of religious trends have highlighted the need to strengthen the integrity and diversity of the modern world, the actualization of the problems associated with the formation of philosophical, civil and patriotic beliefs of the younger generation. In this regard, this article devotes on the development of structural and functional model of formation of patriotism at schoolchildren by means of folk pedagogy. The leading approaches to the study of this problem were the student-centered and axiological approaches to comprehensively cover this problem. The article presents a model of patriotic qualities of schoolchildren by means of folk pedagogy, which includes the target, procedural, substantive, organizational and methodical, efficiently-evaluative components that together provide effective formation of patriotic qualities of schoolchildren. This model can be applied in the practice of primary school teachers in the preparation of students of pedagogical high schools to perform the functions of primary school teachers, as well as in-service teacher training system.